Bahasa Arab sebagai Simbol Identitas Santri: Analisis Motivasi Belajar Berbasis Eksistensi Sosial-Religius pada Mahasiswa Pendidikan Bahasa Arab Universitas Kiai Abdullah Faqih Gresik - Muhammad Farih; Adi Juiarto; Muhammad Alawy; Muhamad Syaifiudin; Mas Achmad Ali Akbar; Muhammad A'inul Haq; Ahmad Nuruddin (KURAS Institute, 2025)
This study investigates the dynamics of learning motivation among Arabic Language Education undergraduates at Kiai Abdullah Faqih University who possess a distinct santri (Islamic boarding school student) background. Specifically, it explores the intricate interplay between socio-religious motivation, identity construction, and the transitional friction experienced when moving from traditional pesantren environments to higher education. Utilizing a mixed-methods design, empirical data were gathered via structured questionnaires. The findings reveal that the Arabic language functions not merely as a linguistic tool, but as a crucial socio-religious identity marker and vital cultural capital underpinning the students' prospective roles as religious scholars and educators. Intrinsic religious orientation—chiefly the aspiration to comprehend the Qur'an and Kitab Kuning (classical Islamic texts)—serves as the primary behavioral driver, whereas extrinsic motivators, such as grade point averages (GPA), exert negligible influence. Conversely, the study uncovers a distinct